2014
DOI: 10.1007/978-3-319-08019-2_42
|View full text |Cite
|
Sign up to set email alerts
|

Short Lists with Short Programs in Short Time – A Short Proof

Abstract: Bauwens, Mahklin, Vereshchagin and Zimand [1] and Teutsch [5] have shown that given a string x it is possible to construct in polynomial time a list containing a short description of it. We simplify their technique and present a shorter proof of this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…More precisely, [BMVZ13] showed that one can compute lists of quadratic size guaranteed to contain a program of x whose length is C(x) + O(1) and that one can compute in polynomialtime a list guaranteed to contain a program whose length is additively within C(x) + O(log n). [Teu14] improved the latter result by reducing the O(log n) term to O(1) (see also [Zim14] for a simpler proof).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…More precisely, [BMVZ13] showed that one can compute lists of quadratic size guaranteed to contain a program of x whose length is C(x) + O(1) and that one can compute in polynomialtime a list guaranteed to contain a program whose length is additively within C(x) + O(log n). [Teu14] improved the latter result by reducing the O(log n) term to O(1) (see also [Zim14] for a simpler proof).…”
Section: Introductionmentioning
confidence: 94%
“…The size of the list in [BMVZ13] is quadratic in n and in fact in the same paper it is shown that this is optimal because any effectively computed list that contains a program that is additively c close to optimal length must have size Ω(n 2 /(c + 1) 2 ) (for any c). The size of the list in the polynomial-time construction from [Teu14] is n 7+ǫ and [Zim14] improves it to O(n 6+ǫ ). We show here that the size of the list can be linear, thus beating the above quadratic lower bound, if we allow probabilistic computation, in fact even polynomial-time probabilistic computation.…”
Section: Introductionmentioning
confidence: 99%
“…Quoting from [25]: "Given that the Kolmogorov complexity is not computable, it is natural to ask if given a string x it is possible to construct a short list containing a minimal (plus possibly a small overhead) description of x. Bauwens, Mahklin, Vereshchagin and Zimand [1] and Teutsch [21] show that, surprisingly, the answer is YES. Even more, in fact the short list can be computed in polynomial time.…”
Section: Short Listsmentioning
confidence: 99%
“…Moreover, similar lists with slightly weaker parameters can actually be constructed in polynomial time. Teutsch [Teu], Zimand [Zim14] and Bauwens and Zimand [BZ14] have obtained polynomial-time constructions with improved parameters.…”
Section: Occam's Razor For Algorithmsmentioning
confidence: 99%